Pengaruh Penambahan Serat Ijuk Terhadap Kuat Tekan Beton - Sidabutar, Ros Anita; Simanjuntak, Johan Oberlyn; Simangunsong, Josua Marganda (LPPM Universitas HKBP Nommensen, 2022)
Concrete is one of the construction materials consisting of a mixture of coarse aggregate and fine aggregate as a filling material, as well as cement and water as a binder. With the addition of fiber as a partial replacement of cement to obtain a cheaper cost, for simple buildings. With partial replacement of cement with fiber in normal concrete, which aims to determine the effect of partial replacement of cement with fiber against the compressive strength of concrete. By comparing the length variation of fibers which are respectively 4 cm, 6 cm, 8 cm and fibers taken 2% of the weight of cement. Where the calculation analysis (mix desing) using SNI 7656-2012 (procedure for making normal concrete mix plan). Mix design is done in order to determine the proportion of the mixture is done with strong concrete quality planned. The test object is a cylinder with a diameter with a diameter of 15 cm and height of 30 cm. From the results obtained the replacemen of some of the cement with fibers. Where the test results of normal concrete slump of 10 cm, fiber concrete measuring 4 cm by 10 cm, fiber conrete measuring 6 cm byy 9.8 cm and fiber concrete measuring 8 cm by 9.7 cm. And the maximum compressive strength test results obtained decreased, the test value of cylindrical concrete without the addition of fiber of 27.08 MPa, where the compressive strength of concrete by using 2% fibers with a length of 4 cm of 26.70 MPa, concrete fiber 6 cm of 25.94 MPa, and for fiber 8 cm of 24.72 MPa. So that the compressive strength of concrete that occurs decreases from normal concrete without the addition of fibers.